Fusões e aquisições na indústria jornalística brasileira : trade offs e visão do jornalista - Vieira, Leandro José (2019)
This paper aims to understand how mergers and acquisitions operations can bring a positive logic to the Brazilian journalistic industry, especially with regard to media management studies. For that, a multidisciplinary theoretical foundation was used, covering areas of knowledge such as Administration, Management, Strategy, Sociology of Journalism, Media Economics and Media Management. Among the main results achieved by this study, we highlight the perception that the journalist is open, in a positive sense, to mergers and acquisitions in the Brazilian information industry. It was also detected that journalists are willing to do journalism with a view to obtaining results that go beyond the editorials. In-depth interviews with four executive journalists in large journalism firms and a survey of approximately 100 non-executive journalists were used to obtain the results of this research. As an academic contribution, this work hopes to increase the studies of media management; as managerial, hopes to help journalism companies understand how mergers and acquisitions can spell growth engines for journalism.